Fear and Anxiety of COVID-19, Stress and Health Perception. A Predictive Model in Ecuadorian Hospital Patients - Sánchez-Vélez, Hernán; Moreta-Herrera, Rodrigo (Anales de Psicología / Annals of Psychology, 2022)
Objective: To develop a predictive model of mental health based on fear and anxiety of COVID-19 and perceived stress in a sample of primary care patients in Ecuador. Method: A correlational, comparative and predictive study applying Anxiety to Coronavirus, Fear of Covid-19, Perceived Stress and General Health scales, and SEM as a data analysis technique. Participants: 460 primary care hospital patients (38.9% men and 61.1% women) from Ambato and Quito cities, between 18 and 79 years old (M = 36 years; SD = 14.48). Results: Data suggest the presence of moderate levels of fear of COVID-19 and stress and low levels of anxiety to COVID-19. The most prevalent symptoms are somatization and anxiety-insomnia. The relationship of fear and anxiety to COVID-19 and perceived stress with mental health discomfort is confirmed. Fear and anxiety about COVID-19 predict perceived stress and this, in turn, predicts mental health with a 41.2% of explained variance. Conclusion: Fear and anxiety about COVID-19 are predictors of stress, and stress is a predictor of psychological symptoms and mental health discomfort in Ecuadorian primary care patients.